Policy Requirements for the Prevention and Management of Fetal Alcohol Spectrum Disorder in South Africa: A Policy Brief - Adebiyi, Babatope O.; Mukumbang, Ferdinand C.; Beytell, Anna-Marie (Frontiers in Public Health, 2021)
This policy brief is aimed to guide policymakers in developing a comprehensive and multi-sectoral policy for the prevention and management of fetal alcohol spectrum disorder (FASD). FASD is a leading source of non-genetic developmental and intellectual disability and is usually associated with primary and secondary disabilities. South Africa has been identified to have the highest reported prevalence of FASD in the world. Nevertheless, evidence shows that there is no specific policy for FASD, albeit there are clauses that could be attributed to its prevention and management in other existing policies. In this brief, we present a guideline to inform programmes and interventions to tackle the FASD problem in South Africa and other relevant contexts through developing a policy.